IMPLEMENTASI TOLERANSI SUKU AGAMA DAN RAS - Dutatiska, Chieta Lara; R, Marmawi; Amalia, Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the implementation of ethnic, religious, and racial tolerance in Cahaya Bangsa PAUD, Seventeen District, Bengkayang Regency. This form of research uses a qualitative descriptive method. The subjects of this study were the principal, deputy principal, 2 Kindergarten teachers A and B. The data collection techniques used were interviews, observation, and documentation. Data analysis used is data collection, data reduction, data presentation, and drawing conclusions. Techniques for checking the validity of the data are triangulation and member checks. The general results of the study show that the implementation of ethnic, religious and racial tolerance has its forms, supporting and inhibiting factors. The results of the research in particular are: 1. Forms of implementation of ethnic, religious, and racial tolerance in Cahaya Bangsa PAUD are varied, such as exemplifying, giving appreciation, good prejudice, mutual respect, regardless of ethnicity, genes, appearance, culture, beliefs. 2. Supporting factors in Cahaya Bangsa PAUD are mutual respect, respect, having a high sense of caring, strengthening friendship, helping others regardless of ethnicity, religion, and race between students. While the inhibiting factor is the low tolerance which results in mutual indifference between students. The conclusion is to set an example of growing appreciation, not prejudice, and building cooperation with other schools that have religious teachers according to the students' religion.